The home office children's department: implementing the 1948 Children's Act, 1950-1970 - Jim Goddard (Scottish Journal of Residential Child Care)
It is now little remembered that the UK’s Home Office was once responsible for overseeing the state care of children in England and Wales. During the 1950s and 1960s, the Home Office children’s department issued a series of detailed reports that monitored the implementation of the modernising measures of the 1948 Children Act (an Act that also applied to Scotland). Evolution in the provision of children’s homes, in both the state and voluntary sectors, features strongly in the article, since the shift away from large institutions to smaller homes and to foster care was a central aim of the 1948 Act. This article outlines some of the main developments during this period, as described in these reports. Its main purpose is to illustrate the value of these reports and thereby encourage researchers to engage with them as primary sources on the history of residential childcare in the UK.